2019
DOI: 10.4038/jbs.v6i1.42
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of sustainable tourism in ancient cities: a case study based on Kandy, Sri Lanka

Abstract: Within the extensive body of tourism literature, successful implication of sustainable tourism and obstacles to its practices in the developing world are emerging themes. This paper critically investigates challenges to sustainable tourism in the world heritage sites with special references to Kandy situated in Central Province of Sri Lanka. Through adopting a qualitative research method, a key issue for discussion in this paper is challenge to sustainable tourism in Kandy. Consequently, this paper provides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Acclaimed as one of Sri Lanka's most prominent tourism des�na�ons, Kandy is a UNESCO World Heritage city renowned for its unique religious, cultural, and natural offerings (Welagedara, 2016). As the provincial capital of the Central Province, Kandy's incredible tourism product is supplemented with all auxiliary services and ameni�es to support the tourism industry (Sivesan, 2019). Moreover, as per (SLTDA, 2023) records, Kandy currently has a total room inventory of 3,786 rooms, accoun�ng for 7.5% of the en�re room inventory in the country, making the city a prominent des�na�on from a hospitality perspec�ve as well.…”
Section: Geographic Locationmentioning
confidence: 99%
“…Acclaimed as one of Sri Lanka's most prominent tourism des�na�ons, Kandy is a UNESCO World Heritage city renowned for its unique religious, cultural, and natural offerings (Welagedara, 2016). As the provincial capital of the Central Province, Kandy's incredible tourism product is supplemented with all auxiliary services and ameni�es to support the tourism industry (Sivesan, 2019). Moreover, as per (SLTDA, 2023) records, Kandy currently has a total room inventory of 3,786 rooms, accoun�ng for 7.5% of the en�re room inventory in the country, making the city a prominent des�na�on from a hospitality perspec�ve as well.…”
Section: Geographic Locationmentioning
confidence: 99%
“…Region-based international tourism and domestic should be encouraged. The domestic tourism sector has a significant impact on sustainable tourism development in the country (Sivesan, 2019). Sri Lankan tourism should pay more attention to developing domestic tourism in the post COVID -19 period.…”
Section: Sltda Should Step To Work With the Ministry Of Health And In...mentioning
confidence: 99%
“…On the other hand, as tea, rubber and coconut are heavily affected, Sri Lanka is planning to develop tourism. As a result, Sri Lanka became one of the best tourist places in Asia and the third biggest forex earner (Sivesan, 2019). Aslam (2000) found that there was a long-run association between Information Communication Technology (ICT) and Tourism demand through exploratory analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Effective governance and sustainable tourism practices are crucial for the survival and prosperity of such destinations. The literature underscores the importance of a holistic approach to address the complexities of governance and sustainable development in archipelagic environments (Connell, 2018;Nižić et al, 2010;Roscher et al, 2023;Sivesan, 2019). The Sumenep region presents a critical need for detailed examination of governance structures and tourism management practices that balance economic development with environmental conservation, considering the diverse local dynamics (Dagold & Stimers, 2024;Hopwood et al, 2005).…”
Section: Introductionmentioning
confidence: 99%